1988
DOI: 10.1212/wnl.38.11.1728
|View full text |Cite
|
Sign up to set email alerts
|

Sensory form of acute polyneuritis

Abstract: A patient presented with severe sensory loss and ataxia with total arreflexia, and elevation of CSF protein with pleocytosis. At autopsy there was extensive lymphocytic infiltration of nerves and posterior roots, sparing the anterior roots. Teased fiber preparation of nerve showed a demyelinating lesion. There were no abnormalities in the CNS. The condition appears to be an acute sensory polyneuritis bearing a close relationship to acute Guillain-Barré syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Cerebrospinal fluid analysis and electrophysiological tests are compatible with Guillain-Barré syndrome 8889 A necropsy study showed demyelination, with mononuclear cell infiltration of nerves and posterior roots 89…”
Section: Clinicopathological Typesmentioning
confidence: 95%
“…Cerebrospinal fluid analysis and electrophysiological tests are compatible with Guillain-Barré syndrome 8889 A necropsy study showed demyelination, with mononuclear cell infiltration of nerves and posterior roots 89…”
Section: Clinicopathological Typesmentioning
confidence: 95%
“…In others, evidence of demyelination was confined to the terminal latencies, as observed in previously reported cases. [9][10][11] This is understandable, given the nature of the clinical presentation of sensory GBS. The difficulty in demonstrating demyelination in sensory nerve conduction is due to the technical limitation of sensory NCS performed with surface electrodes.…”
Section: (M In 2; All In 6)mentioning
confidence: 99%
“…10 At autopsy, there was extensively lymphocytic infiltration of nerves and posterior roots, with sparing of the anterior roots. Teased fiber preparation of nerve showed a demyelinating lesion.…”
mentioning
confidence: 99%
“…The six patients had a good prognosis, considering the effects of the small fiber damage. Dawson et al (8) described a case of sensory GBS in which the patient exhibited abnormal sensation and joint position sense, vibratory sensory abnormalities and ataxia. Certain patients may exhibit subjective weak limb muscle strength, and electrophysiology tests can show demyelination of the involved motor fiber, which is also considered as a lesion in the large sensory fiber.…”
Section: Discussionmentioning
confidence: 99%